Geographic distribution and morphological variation in Mimon bennettii (Chiroptera, Phyllostomidae) - Gregorin, Renato; Capusso, Guilherme L. [UNESP]; Furtado, Vanessa R. (Fundação Zoobotanica Rio Grande Sul, Museu Ciencias Naturais, 2008)
We studied discrete and quantitative data from SS specimens of the subgenus Mimon previously identified as Mimon bennettii (Gray. 1838) and M. (:cozumelae Goldman, 1914 from diverse parts of their ran-c. Our data indicate that specimens of Mimon bennetii in Brazil presented geographic variation in morphometrical characters and mosaic variation in qualitative traits. Specimens' from the Cerrado biome collected in Brazilian states like Piaui. Tocantins. and Goias have longer forearms than those distributed in the Atlantic and Amazon forested domains. Based on morphometrics, its showed by t-tests. specimens of M. bennettii from the Brazilian Cerrado resemble phenetically more With M. cozumelae than the M. bennettii from Atlantic Forest. Characters presently used to diagnosis M. cozumelae also were also recorded to M. bennettii in diverse parts of Brazil, making that validity of M. cozumelae questionable based on this kind of traits. This research also updated tire geographic distribution to the M. bennettii in Brazil.
Distribuição geográfica e variação morfológica em Mimon bennettii (Chiroptera, Phyllostomidae)
Keywords: Morphology; morphometry; Cerrado; Atlantic Forest; distribution